Distance Learning and Students With Extensive Support Needs: (Re)Defining Access to Education From a Distance. Issue 1 (February 2022) - Hanreddy, Amy
Students with Extensive Support Needs (ESN) experience multiple barriers in accessing distance learning educational programs during school closures in the context of the COVID-19 pandemic. These barriers include inaccessible formats, a lack of access to adequate support to access instruction, and a lack of available assistive technology. Access issues may result in further isolation of students and reduced access to general education peers and curriculum. Promising practices include close collaboration with families, connecting Individualized Education Program (IEP) goals to students' daily routines, supporting access to the general education curriculum, strategic participation in online classes, meaningful engagement with typical peers, and the adaptation of progress monitoring strategies for distance learning formats.